Revisiting the Impact of Stellar Magnetic Activity on the Detectability of Solar-Like Oscillations by Kepler - Mathur, Savita; García, Rafael A.; Bugnet, Lisa; Santos, Ângela R.G.; Santiago, Netsha; Beck, Paul G. (Frontiers in Astronomy and Space Sciences, 2019)
Over 2,000 stars were observed for one month with a high enough cadence in order to look for acoustic modes during the survey phase of the \kep\ mission. Solar-like oscillations have been detected in about 540 stars. The question of why no oscillations were detected in the remaining stars is still open. Previous works explained the non-detection of modes with the high level of magnetic activity of the stars. However, the sample of stars studied contained some classical pulsators and red giants that could have biased the results. In this work, we revisit this analysis on a cleaner sample of main-sequence solar-like stars that consists of 1,014 stars. First we compute the predicted amplitude of the modes of that sample and for the stars with detected oscillation and compare it to the noise at high frequency in the power spectrum. We find that the stars with detected modes have an amplitude to noise ratio larger than 0.94. We measure reliable rotation periods and the associated photometric magnetic index for 684 stars out of the full sample and in particular for 323 stars where the amplitude of the modes is predicted to be high enough to be detected. We find that among these 323 stars 32% of them have a level of magnetic activity larger than the Sun during its maximum activity, explaining the non-detection of acoustic modes. Interestingly, magnetic activity cannot be the primary reason responsible for the absence of detectable modes in the remaining 68% of the stars without acoustic modes detected and with reliable rotation periods. We investigate metallicity, inclination angle of the rotation axis, and binarity as possible causes of low mode amplitudes. Using spectroscopic observations for a subsample, we find that a low metallicity could be the reason for suppressed modes. No clear correlation with binarity nor inclination is found. We also derive the lower limit for our photometric activity index (of 20-30\,ppm) below which rotation and magnetic activity are not detected. Finally, with our analysis we conclude that stars with a photometric activity index larger than 2,000ppm have 98.3% probability of not having oscillations detected.